2008
DOI: 10.1002/mmng.200700011
|View full text |Cite
|
Sign up to set email alerts
|

A new body mass estimation ofBrachiosaurus brancaiJanensch, 1914 mounted and exhibited at the Museum of Natural History (Berlin, Germany)

Abstract: Body mass and surface areas are important in several aspects for an organism living today. Therefore, mass and surface determinations for extinct dinosaurs could be important for paleo‐biological aspects as well. Based on photogrammetrical measurement the body mass and body surface area of the Late Jurassic Brachiosaurus brancai Janensch, 1914 from Tendaguru (East Africa), a skeleton mounted and exhibited at the Museum of Natural History in Berlin (Germany), has been re‐evaluated. We determined for a slim type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 25 publications
(52 reference statements)
0
23
0
Order By: Relevance
“…Gunga et al (2008) had already concluded that the coelomic cavity of a 38 tonne sauropod dinosaur (Brachiosaurus brancai ), which they assumed to harbour a volume of 32 m 3 according to their body size reconstructions, provided more space than that necessary for most of the organs of this cavity (including a proportion of the skeleton, blood volume and muscle mass, but without accounting for mesenteries, coelomic fat and reproductive organs), which they estimated at 21 m 3 . Using our 'linear' approach and the reptile functions (table 2), and adopting a linear approach based on the mammal functions used by Gunga et al (2008) for those organs that we could not include in our study, we arrive at a volume estimate of only 17.6 m 3 . Evidently, even when considering that mesenteries, fat and reproductive organs are not included in these calculations, the present data allow for a dramatic increase in organ masses in the reconstruction of sauropod dinosaurs.…”
Section: -3mentioning
confidence: 99%
See 4 more Smart Citations
“…Gunga et al (2008) had already concluded that the coelomic cavity of a 38 tonne sauropod dinosaur (Brachiosaurus brancai ), which they assumed to harbour a volume of 32 m 3 according to their body size reconstructions, provided more space than that necessary for most of the organs of this cavity (including a proportion of the skeleton, blood volume and muscle mass, but without accounting for mesenteries, coelomic fat and reproductive organs), which they estimated at 21 m 3 . Using our 'linear' approach and the reptile functions (table 2), and adopting a linear approach based on the mammal functions used by Gunga et al (2008) for those organs that we could not include in our study, we arrive at a volume estimate of only 17.6 m 3 . Evidently, even when considering that mesenteries, fat and reproductive organs are not included in these calculations, the present data allow for a dramatic increase in organ masses in the reconstruction of sauropod dinosaurs.…”
Section: -3mentioning
confidence: 99%
“…As sauropods are thought to have heterogeneous (avian-type) lungs with an air sac system ), a part of the space in the coelomic cavity was probably filled with these air sacs. In birds, the lungs and air sacs may account for as much as 20 per cent of the total body volume (King 1966); in the 38 tonne sauropod of Gunga et al (2008), with an estimated total volume of approximately 47.6 m 3 , this would represent a total lung and air sac volume of 9.5 m 3 . Even if we assume that the majority of this volume was placed within the coelomic cavity, the reconstruction would still allow for theoretical increases in any organ masses.…”
Section: -3mentioning
confidence: 99%
See 3 more Smart Citations